Performance comparison of Zr-based and Bi-based erbium-doped fiber amplifiers - Paul, M.C.; Harun, Sulaiman Wadi; Huri, N.A.D.; Hamzah, A.; Das, S.; Pal, M.; Bhadra, S.K.; Ahmad, Harith; Yoo, S.; Kalita, M.P.; Boyland, A.J.; Sahu, J.K. (Optical Society of America, 2010)
In this Letter, we present a comprehensive comparison of the performance of a zirconia-based erbium-doped fiber amplifier (Zr-EDFA) and a bismuth-based erbium-doped fiber amplifier (Bi-EDFA). The experimental results reveal that a Zr-EDFA can achieve comparable performance to the conventional Bi-EDFA for C-band and L-band operations. With a combination of both Zr and Al, we could achieve a high erbium-doping concentration of about 2800 ppm (parts per million) in the glass host without any phase separations of rare earths. The Zr-based erbium-doped fiber (Zr-EDF) was fabricated using in a ternary glass host, zirconia-yttria-aluminum codoped silica fiber through a solution-doping technique along with modified chemical vapor deposition. At a high input signal of 0 dBm, a flat gain at average value of 13 dB is obtained with a gain variation of less than 2 dB within the wavelength region of 1530-1575 nm and using 2 m of Zr-EDF and 120 mW pump power. The noise figures are less than 9.2 at this wavelength region. It was found that a Zr-EDFA can achieve even better flat-gain value and bandwidth as well as lower noise figure than the conventional Bi-EDFA. (C) 2010 Optical Society of America